2011
DOI: 10.1007/s00436-011-2581-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of peripheral blood T lymphocyte subsets in Chinese rhesus macaques with repeated or long-term infection with Plasmodium cynomolgi

Abstract: T lymphocytes play a vital role in antimalaria immunity, but there is little information about the role of T cells in malaria infection. In order to explore the profile of T cells in malaria immunity, we infected Chinese rhesus macaques with the malaria parasite (Plasmodium cynomolgi) and examined the dynamics of T cell subsets. Both repeated and long-term infections were involved. Our results showed that the monkeys in the repeated infection group acquired protective immunity through primary infection, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…to study infectious diseases including simian immunodeficiency virus/ human immunodeficiency virus, avian influenza, malaria, plague, and severe acute respiratory syndrome, as well as studies of xenotransplantation, stem cell therapies, reproduction, and neurobiology (Shen et al 2007;Chen et al 2009Chen et al , 2011Chen et al , 2012Choi et al 2011;Liu et al 2011;Tian et al 2011;Wei et al 2011;Hutnick et al 2012;Li et al 2012b;Ling et al 2013;Mumbauer et al 2013). Yet comparatively little is known about the immunogenetics of these animals.…”
mentioning
confidence: 99%
“…to study infectious diseases including simian immunodeficiency virus/ human immunodeficiency virus, avian influenza, malaria, plague, and severe acute respiratory syndrome, as well as studies of xenotransplantation, stem cell therapies, reproduction, and neurobiology (Shen et al 2007;Chen et al 2009Chen et al , 2011Chen et al , 2012Choi et al 2011;Liu et al 2011;Tian et al 2011;Wei et al 2011;Hutnick et al 2012;Li et al 2012b;Ling et al 2013;Mumbauer et al 2013). Yet comparatively little is known about the immunogenetics of these animals.…”
mentioning
confidence: 99%
“…Our previous study using the rhesus monkey model indicated that Pc infection activated CD4+ T cells in SIV-negative animals [ 7 ]. In the present study, we examined activation markers of CD4+ T cells in SIV-positive animals under ART, including HLA-DR and CD38 co-expression on CD4+ T cells and plasma cytokine concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the limited supply of well-characterized Indian rhesus macaques, scientists have begun using Chinese rhesus macaques to study infectious disease such as HIV/SIV, influenza, and malaria, in addition to xenotransplantation and stem cell therapies (Southwick and Siddiqui 1994; Chen et al 2011; Chen et al 2009; Choi et al 2011; Hutnick et al 2012; Li et al 2012; Ling et al 2013; Mumbauer et al 2013; Wei et al 2011). However, characterization of MHC class I sequences in the Chinese rhesus macaque population remains incomplete.…”
Section: Introductionmentioning
confidence: 99%